Canines vaccinated against visceral leishmaniasis develop a serological response to the Leishmania braziliensis antigen - Julia de Assis Pinheiro; Silas Garcia Giori; Sayanne Luns Hatum de Almeida; Rafael Assis de Souza; Ana Paula Madureira; Marcos Santos Zanini (Semina: Ciências Agrárias, 2018)
American cutaneous leishmaniasis (ACL) is a zoonosis caused by Leishmania, a protozoan. Common antigens occur in the strains found in America, which allow antigenic cross-reactivity. Therefore, multivalent vaccines can be used for this pathogen. In this study, we investigated the efficacy of two different commercial vaccines for visceral leishmaniasis to induce an immune response to the soluble L. (Viannia) braziliensis antigens. In 2014, 70 seronegative dogs from the municipality of Iúna (Espírito Santo State, Brazil) were vaccinated and serologically evaluated by ELISA and immunoblotting by using the soluble antigen of L. braziliensis. Of the 121 dogs initially selected, only 70 received vaccination because 51 dogs tested positive by ELISA, yielding a positive frequency of 42.14% in the asymptomatic group. These 70 dogs were divided into two equal groups and administered three doses of each vaccine, according to the manufacturers’ instructions. We found that the sera of dogs immunized with three doses of both vaccines A and B had antibodies against the soluble antigens of L. (V.) braziliensis, as determined by ELISA and immunoblotting 120 days post vaccination. Antibodies produced in response to vaccines A and B were found in 22/35 and 18/35 serum samples, respectively, at T1 (120 days), while 7/35 and 4/35 serum samples tested positive at T2 (240 days). Furthermore, immunoblotting allowed us to differentiate between vaccinated and asymptomatic dogs.